Peningkatan Pengetahuan Pencegahan serta Pengobatan Tuberculosis Sensitif dan Resisten Obat Pada Perkumpulan Wanita Di Jayapura : (To increase knowledge on prevention and treatment of drug-sensitive and drug-resistant tuberculosis among women in Jayapura) - Sianturi, Elfride Irawati; Lingga, Irene Sondang; Appa, Felycitae Ekalaya; Barus, Andre anusta (Sam Ratulangi University, 2024)
ABSTRACT The increasing incidence of Tuberculosis (TB) in Papua and the delayed treatment of complex TB need programs to solve the problems by increasing knowledge in community, especially among women. The programs should be conducted routinely and on a scheduled basis. Failure to treat TB remains high and this will lead to resistance. The impact of resistance is likely to lead to drug-resistant TB (DR-TB), which requires longer treatment and severe side effects. The method used in this acctivities was to conduct routine counseling on the symptoms of TB, its treatment and access to treatment of this disease at the nearest health center. A total of 26 mothers participated in routine counseling where there was a significant change before and after counseling. Increasing knowledge routinely with counseling can provide good results in TB prevention in the community and there is a possibility that mothers can become driving agents in finding new TB patients and helping TB suspects in their treatment by becoming supervised treatment. ABSTRAKI Meningkatnya angka kejadian Tuberkulosis (TB) di Papua serta terlambatnya pengobatan TB yang kompleks menjadi pentingnya kegiatan peningkatan pengetahuan masyarakat terutama para ibu dalam mengenali gejala TB. Hal ini menjadi sebuah kekhawatiran mengingat gagalnya pengobatan TB yang akan menyebabkan resistensi. Hal ini akan berdampak pada penemuan TB Resisten Obat (RO) yang membutuhkan pengobatan lebih lama serta efek samping yang berat. Metode yang dilakukan dalam pengabdian ini adalah dengan melakukan penyuluhan secara rutin mengenai gejala TB, pengobatannya serta akses pengobatan penyakit ini di puskesmas terdekat. Sebanyak 26 ibu-ibu mengikuti penyuluhan secara rutin dimana bahwa adanya perubahan sebelum dan sesudah penyuluhan terjadi perubahan secara signifikan. Peningkatan pengetahuan secara rutin dengan penyuluhan dapat memberikan hasil yang baik dalam penanggulangan TB di komunitas serta adanya kemungkinan para ibu dapat menjadi agen penggerak dalam penemeuan pasien TB yang baru serta membantu suspek TB dalam pengobatannya dengan menjadi pengawas minum obat. Keywords: TB; Drug Resistance, Counselling Community, Jayapura